2022
DOI: 10.3390/children9030413
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Phthalate Biomarkers during Pregnancy, and Maternal Endocrine Parameters in Association with Anthropometric Parameters of Newborns

Abstract: Adverse birth outcomes present risk factors resulting in neonatal morbidity and mortality. Sufficient maternal hormonal concentrations are crucial for normal foetal development. Previous studies have shown a relationship between phthalate exposure and maternal hormonal levels during pregnancy. This study aims to investigate if neonatal anthropometric parameters are associated with maternal endocrine parameters during the ≤15th week of gestation and the third trimester of pregnancy concerning phthalate exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 77 publications
(100 reference statements)
0
2
0
Order By: Relevance
“…Participation was anonymous and voluntary, and all probands signed informed consent prior to involvement. The sample collection and exclusion criteria were described elsewhere [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…Participation was anonymous and voluntary, and all probands signed informed consent prior to involvement. The sample collection and exclusion criteria were described elsewhere [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…It is shown that DiBP has a toxic effect on the reproductive system, leading to a decrease in the level of male sex hormones and miscarriage [9]. A study on the effect of phthalates on maternal hormone levels during pregnancy shows an association with birth outcome [10]. In connection with Chemosensors 2023, 11, 393 2 of 16 the detected effects, the maximum allowable concentrations were established, which for DiBP is 300 µg/L [11].…”
Section: Introductionmentioning
confidence: 98%